2008
DOI: 10.1158/1078-0432.ccr-07-5147
|View full text |Cite
|
Sign up to set email alerts
|

DNA Double-Strand Break Repair of Blood Lymphocytes and Normal Tissues Analysed in a Preclinical Mouse Model: Implications for Radiosensitivity Testing

Abstract: Purpose: Radiotherapy is an effective cancer treatment, but a few patients suffer severe radiation toxicities in neighboring normal tissues.There is increasing evidence that the variable susceptibility to radiation toxicities is caused by the individual genetic predisposition, by subtle mutations, or polymorphisms in genes involved in cellular responses to ionizing radiation. Doublestrand breaks (DSB) are the most deleterious form of radiation-induced DNA damage, and DSB repair deficiencies lead to pronounced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
97
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 50 publications
8
97
0
1
Order By: Relevance
“…In contrast to these reports, our γH2AX data showed activation of the DNA damage response pathway and involvement of ATM, even at low doses of radiation. 33 Nakamura et al 34 also demonstrated significant and dosedependent numbers of γH2AX foci in A-T cells, suggesting that DNA damage was not completely repaired during low-dose radiation. These findings go in line with Short et al, who found that ATM-dependent signaling to downstream targets, such as TP53, CHK1 and CHK2, occurs even at low doses of 0.2 Gy IR.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these reports, our γH2AX data showed activation of the DNA damage response pathway and involvement of ATM, even at low doses of radiation. 33 Nakamura et al 34 also demonstrated significant and dosedependent numbers of γH2AX foci in A-T cells, suggesting that DNA damage was not completely repaired during low-dose radiation. These findings go in line with Short et al, who found that ATM-dependent signaling to downstream targets, such as TP53, CHK1 and CHK2, occurs even at low doses of 0.2 Gy IR.…”
Section: Discussionmentioning
confidence: 99%
“…Third, most cell lines in culture exhibit high background foci levels, which make it difficult to analyze DSB repair after low doses in vitro (26). Thus, we refined our previously published methodological approach to investigate DSB repair after low radiation doses in various tissues of irradiated mice (34). Using the analysis of 53BP1 and γ-H2AX foci in tissue sections of the heart, small intestine, and kidney, we were able to show that mice that underwent whole-body irradiation with 10 mGy fail to repair DSBs efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…The induction yield of about 7 foci per cell per 1 Gy at 10 min post-IR is similar to that of our previous study (34) but substantially lower than the level of 15-20 foci per 1 Gy typically observed for human cells in culture (28). We have previously suggested that this difference may reflect that mouse cells have a 20% lower DNA content than human cells, that additional foci loss can occur during the time necessary to retrieve and fix the organs, and that foci scoring in a cross-section of cells embedded in a tissue sample will significantly underestimate the true foci numbers (34). The results for γ-H2AX foci were slightly more variable than for 53BP1 foci but confirmed our finding that foci in tissues are induced linearly with a dose between 10 mGy and 1 Gy (about 0.07, 0.6, and 8 γ-H2AX foci per cell at 10 min after 10 mGy, 100 mGy, or 1 Gy, respectively) (Fig.…”
Section: Pretreatment Of Confluent Primary Human Fibroblasts With H 2mentioning
confidence: 92%
See 1 more Smart Citation
“…Kinetics of disappearance of the Á-H2AX foci in lymphocytes is representative for DNA DSB repair in other tissues. This has been demonstrated by means of mouse strains carrying subtle polymorphisms or mutations in genes involved in DNA DSB repair (32).…”
Section: Discussionmentioning
confidence: 99%